The USP8 mutational status may predict drug susceptibility in corticotroph adenomas of Cushing's disease. Issue 2 (February 2016) - Hayashi, Kyohei; Inoshita, Naoko; Kawaguchi, Kohei; Ibrahim Ardisasmita, Arif; Suzuki, Hisanori; Fukuhara, Noriaki; Okada, Mitsuo; Nishioka, Hiroshi; Takeuchi, Yasuhiro; Komada, Masayuki; Takeshita, Akira; Yamada, Shozo
Abstract : Context: Somatic mutations in the ubiquitin-specific peptidase USP8 gene were recently detected in one- to two-third(s) of corticotroph adenomas of Cushing's disease (CD). These mutations may lead to the deubiquitination of EGFR, thereby increasing EGFR signaling, which has been implicated in ACTH hypersecretion. Objective: Our objective was to determine the impact of USP8 mutations on the clinicopathological features of CD. Subjects and methods: USP8 mutations as well as clinicopathological characteristics were examined in 60 corticotroph adenomas including 15 Crooke's cell adenomas (CCAs), a rare histological variant presenting with generally aggressive behavior, using qRT-PCR and/or immunohistochemistry. Results: USP8 mutations were exclusively detected in women, except for one case, with a prevalence of 42.2% in non-CCA and 13.3% in CCA (overall 35%). Clinically well-behaved presentations including microadenoma and curative resection were more common in mutated cases. The expression of EGFR was not associated with the mutation status. In contrast, mutated tumors expressed significantly higher levels of POMC, SSTR5, and MGMT. Conclusions: Microadenomas that strongly express POMC were common among mutated tumors, which may lead to the mechanisms by which very small adenomas secrete excess ACTH to present overt CD. While USP8 mutations were less likely to enhance tumorous ACTH hypersecretion via EGFR-mediated activation, the presence of USP8 mutations may predict favorable responses to the somatostatin analog pasireotide, which exhibits high affinity for SSTR5. In contrast, non-mutated aggressive tumors such as CCA may respond better to the alkylating agent temozolomide because of their significantly weak expression of MGMT.